Participation of Rural Women in Livestock Management Activities in Cooch Behar District of West Bengal (Indian Journal of Extension Education, 2013)
A study was carried out to ascertain the participation of rural women in livestock management, using a pretested structured interview schedule for collecting the relevant information. One hundred and twenty rural women randomly were selected from purposively selected one block and four villages selected randomly. The study revealed that majority of the respondents were of middle aged, illiterate and marginal farmers having low annual income. They belonged to joint family and had agriculture as the main occupation. It was found that majority of the respondents had high level of participation in various activities of livestock management. Age, land holding and livestock possession were found to be positively and significantly correlated with livestock management practices.